UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA DENGAN METODE KOOPERATIF JIGSAW PADA MATERI REPRODUKSI - Dadah Jubaedah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This research was motivated by the low student learning outcomes in the Biology subject of reproductive system material. The research aims to improve the learning outcomes of biology in the reproductive system by applying the jigsaw cooperative method. This type of research is a classroom action research with two cycles. Each cycle is carried out in two meetings. The research subjects were students of class XI MIA MAN 2 Pangandaran. The data collection techniques used were test and non-test. The results showed that the application of the jigsaw cooperative method can improve students' cognitive learning outcomes from an average of 67 in the first cycle to 81.2 in the second cycle. Completeness of learning increased from 10.3% in cycle I to 86.2% in cycle II. Affective learning outcomes increased from 10.3% in cycle I to 27.6% in cycle II. Learning motivation increased from 10.3% in cycle I to 27.6% cycle II. Students belonging to the low category decreased from 10.3% in cycle I to 6.9% in cycle II. This means that the application of the jigsaw cooperative learning model can increase motivation and learning outcomes of class XI MIA 2 MAN 2 Pangandaran on reproductive system material.